Entrepreneurship as a Survival Strategy in an Unequal Distribution Arena Intermediary Traders in Banjarnegara - Megawati Putri (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2026)
Distribution dynamics constitute a crucial yet often overlooked dimension of agrarian systems. State-driven regimes of agrarian inclusion generally assume that farmers’ welfare can be achieved through the expansion of legal access to land, while distribution is treated as a technical domain governed by market mechanisms. This article conceptualizes distribution as a competitive social arena in which actors contest positions, capital, and strategies under conditions of structural uncertainty. Based on qualitative research in Batur Village, Banjarnegara Regency, drawing on in-depth interviews, literature review, and observation the study shows that intermediary traders in the potato trade occupy an ambivalent and vulnerable position. While frequently stigmatized as dominant actors within the distribution chain, they simultaneously face market pressures, price volatility, and limited institutional protection. Intermediary traders develop entrepreneurship as a survival strategy embedded in the distribution arena. Read as a social practice, entrepreneurship emerges not as evidence of successful inclusion, but as an effect of the absence of state institutional protection. It functions as a mechanism through which distributional risks are systematically transferred to local actors. These findings underscore that the distribution arena constitutes a primary site where formal inclusion intersects with subtle forms of exclusion in contemporary agrarian struggles.